Effects of early supplemental parenteral nutrition on new-onset infection in adults with acute severe stroke: a single-center retrospective case–control study - Chen Ma; Zhirong Fan; Xuan Wang; Bian Li; Jingjing Zhao; Xiaogang Kang; Wen Jiang; Fang Yang (BMC Neurology)
Abstract Background Early adequate feeding reduces mortality in patients with acute severe stroke. Supplemental parenteral nutrition (SPN) may address enteral nutrition (EN) deficiency and mitigate the risk of nosocomial infection. The benefit of the EN plus early SPN strategy over the full EN strategy is unknown in acute severe stroke patients. Methods We retrospectively enrolled 20 patients with acute severe stroke in the SPN group who received EN plus early SPN (more than 50% of the energy target within 72 h after admission). Forty control patients in the EN group who received full EN were matched by age, sex and lesion site. The time to new-onset pneumonia or nosocomial infections was analyzed by Student’s t test and the Breslow generalized Wilcoxon test. Results The baseline characteristics did not differ significantly between the SPN group and the EN group, except for higher serum leukocyte counts, neutrophil counts, and neutrophil-to-lymphocyte ratios in the SPN group (P < 0.05). Compared with that in the EN group, the time to new-onset pneumonia was significantly delayed in the SPN group (7.6 days vs. 5.2 days; mean difference, 2.5 days; 95% CI, 0.65 to 4.31; P = 0.009), as was the time to new-onset nosocomial infections (7.1 days vs. 4.8 days; mean difference, 2.3 days; 95% CI, 0.46 to 4.07; P = 0.015). Kaplan–Meier analysis revealed similar cumulative probabilities of new-onset pneumonia and new-onset nosocomial infections in the two groups (P > 0.05). The rates of digestive intolerance events were similar between the two groups (40% in the SPN group vs. 52.5% in the EN group, P = 0.361). Conclusions In patients with acute severe stroke, the application of EN plus early SPN could delay the onset of pneumonia and nosocomial infections especially in the early phase.